2011
DOI: 10.5539/ijbm.v6n4p161
|View full text |Cite
|
Sign up to set email alerts
|

Internet Banking Adoption in Kuala Lumpur: An Application of UTAUT Model

Abstract: Internet banking is becoming a new focuses as the number of internet users is increasing globally and its benefits.
This study aimed to investigate the factors and determinants of internet banking adoption among Malaysian.
Four factors that proposed to influence the adoption from Unified theory of acceptance and use of technology
were included in this study. A total of 200 respondents were collected using convenience sampling. Results of
this study showed that performance expectancy (r = 0.…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
48
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 6 publications
(6 reference statements)
10
48
3
1
Order By: Relevance
“…In the context of this study and from the government employees' department of communication and information and also the community perspective, social influence, and facilitating condition are the povital or dominant variable in the intention to use the lapor sleman mobile application (Table 4). This supports the argument that social influence which they have a positive affect (Foon and Fah, 2011;Indriwati and Haryoto, 2013;Venkatesh, 2013, Xu, 2014, on user behavior to use technology. Besides, the performance expectancy also has emerge as predictor of the particular users behavior.…”
Section: Implication To Theorysupporting
confidence: 75%
See 1 more Smart Citation
“…In the context of this study and from the government employees' department of communication and information and also the community perspective, social influence, and facilitating condition are the povital or dominant variable in the intention to use the lapor sleman mobile application (Table 4). This supports the argument that social influence which they have a positive affect (Foon and Fah, 2011;Indriwati and Haryoto, 2013;Venkatesh, 2013, Xu, 2014, on user behavior to use technology. Besides, the performance expectancy also has emerge as predictor of the particular users behavior.…”
Section: Implication To Theorysupporting
confidence: 75%
“…Social Influence is the extent to which a person perceives that other people around him or her (eg, family and friends) can influence him or her to use a certain technology (Venkatesh et al, 2013). According to the research of (Foon and Fah (2011), social influence has a significant influence on behavioral intention, it is also supported by a research conducted by Indrawati and Haryoto (2015) showing that social influence has a positive influence on behavioral intention. According to Venkatesh et al (2003), social influence is the factor determining behavioral intention directly.…”
Section: Social Influencementioning
confidence: 97%
“…Others studies that examined the relationship between social influence and intentions also confirmed the effect of social influence toward intention (Al-Shafi & Weerakkody, 2010;Esmaili et al, 2011;Maldonado et al, 2011;Rimal et al, 2006;Sok Foon & Chan Yin Fah, 2011). …”
Section: Social Influence and Intentionmentioning
confidence: 82%
“…(2014), Mansour et al (2016), Rodrigues et al (2016), etc.…) which is the adaptation of the Theory of Reason Action (TRA), which was proposed by Fishbein and Ajzen in 1975, Ahmadi and Afrouzi. 2012, Rodrigues et al 2016 and Unified Theory of Acceptance and Use of Technology (UTAUT) developed by Venkatesh et al in 2003. This theory is used very widely for its simplicity, parsimony and robustness (Oshlyansky et al 2007, AbuShanab et al, 2010, Yuen et al, 2010, Foon and Fah, 2011, Venkatesh et al 2012, El-Qirem 2013, Tarhini et al, 2014. The list of the theories used in these reviewed papers is given in Appendix 1.…”
Section: The Applied Theories and Modelsmentioning
confidence: 99%